Faktor-Faktor yang Mempengaruhi Pemberian MP-ASI Pada Anak Usia 6-24 Bulan - Mutiara Wahyuni Manoppo (NUTRIX, 2023)
Babies aged >6 months need more vitamins, minerals, protein and carbohydrates which can’t be fulfilled only with breast milk. Complementary food is an addition that can be given to meet the > 6 months needs. There are some factors that influence complementary foods practices. This review is aimed to find what are the factors that influence the provision of complementary feeding. This study used a PRISMA guidelines. This review conducted by using searching databases Google Scholar, scienceDirect, Springer Link, Proquest and Sage Journal from 2019-2023. The exclusion criteria were article review and studies protocol. 11 articles included in this review. The result shows the influencing factors of complementary food practices are educational background, knowledge, sociocultural and economic factors. The most influencing factors is knowledge of mothers. Needs more attention from the stakeholder to help increase mother knowledge about complementary feeding. Keywords: Baby, Complementary feeding, Influencing Factors Abstrak Bayi berusia > 6 bulan membutuhkan lebih banyak vitamin, mineral, protein, dan karbohidrat yang tidak dapat dipenuhi lagi hanya dengan Air Susu Ibu (ASI). Makanan pendamping ASI (MP-ASI) adalah tambahan yang bisa diberikan untuk memenuhi kebutuhan bayi > 6 bulan. Ada beberapa faktor yang mempengaruhi pemberian makanan pendamping ASI. Tujuan review ini untuk mengetahui apa yang menjadi faktor yang mempengaruhi pemberian MP-ASI. Penelitian ini menggunakan kerangka kerja PRISMA. Pencarian literatur dilakukan pada database google scholar, scienceDirect, Springer Link, Proquest dan Sage Journal dari tahun 2019-2023. Kriteria inklusi pada review ini adalah artikel review dan studi protokol. 11 artikel termasuk dalam review ini. Hasil menunjukkan Faktor yang dapat mempengaruhi ibu dalam pemberian MP-ASI yaitu pendidikan, pengetahuan, sosial budaya dan ekonomi. Faktor paling dominan ialah pengetahuan. Dibutuhkan perhatian yang lebih dari pihak terkait untuk meningkatkan pengetahuan ibu mengenai MP-ASI. Kata Kunci: Balita, Faktor pendukung, Makanan Pendamping ASI.